2018
DOI: 10.1016/j.electacta.2017.12.104
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical switching fluorescence emission in rhodamine derivatives

Abstract: a b s t r a c tThree rhodamine derivatives exhibiting electrofluorochromic properties were investigated by cyclic voltammetry and UVeVis/fluorescence spectroelectrochemistry. Rhodamine 101 (Rh101, compound 1) was used as a reference model. In compound 2, the carboxylate anion of Rh101 was replaced by an alkyne moiety to allow further functionalization. The compound 3 was prepared from 2 by conversion of the alkyne to a triazole group bearing an alkyl chain with an alcohol function. These three rhodamine deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Over the last decades, different strategies have been applied to develop “on‐off” molecular luminescence switches. To the best of our knowledge, charging the molecules has always been reflected either in luminescence annihilation (neutral molecule is the bright state, whereas the charged radical counterpart is dark) [2a] or luminescence tuning (where both neutral and charged states are fluorescent) [9, 10] . The only exception was the oxidation of ex‐TTF‐BODIPY +.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades, different strategies have been applied to develop “on‐off” molecular luminescence switches. To the best of our knowledge, charging the molecules has always been reflected either in luminescence annihilation (neutral molecule is the bright state, whereas the charged radical counterpart is dark) [2a] or luminescence tuning (where both neutral and charged states are fluorescent) [9, 10] . The only exception was the oxidation of ex‐TTF‐BODIPY +.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fluorescence emission could be recovered by switching the potential to a value positive enough to allow the re-oxidation of the radical, establishing the electrofluorochromic properties of R101. Interestingly, multiple On/Off fluorescence switch events could be observed during several minutes, demonstrating the reversibility of the redox activation/deactivation process (Figure 2) [9]. Perylene diimides are another family of redox-fluorescent organic compounds which are popular thanks to their i) emission in the visible spectrum, ii) their strong absorption and fluorescence, iii) their good thermal, chemical, and photochemical stability.…”
Section: Direct Electrochemical Switch Of Organic Fluorescent Moleculesmentioning
confidence: 99%
“…Generally, BODIPY derivatives can be reversibly oxidized into a non-emissive cation radical [13,14]. Among the most relevant modifications of the BODIPY core, the substitution of carbon by nitrogen between the two pyrrolic units shifted the emission in the Rhodamine 101 [9] Perylenediimide [10] N B N F F Bodipy [13][14][15]…”
Section: Direct Electrochemical Switch Of Organic Fluorescent Moleculesmentioning
confidence: 99%
“…More recently, Buriez et al reported electrochemical fluorescence switching of three rhodamine derivatives M10a – c [28]. Compounds M10a , b , and c have λ em at 593, 614, and 600 nm, respectively, but one-electron electrochemical reduction of the three compounds into the radical neutral form resulted in fluorescence quenching.…”
Section: Organic Small Elc Moleculesmentioning
confidence: 99%
“…Compounds M10a , b , and c have λ em at 593, 614, and 600 nm, respectively, but one-electron electrochemical reduction of the three compounds into the radical neutral form resulted in fluorescence quenching. The fluorescence switching is completely reversible and the synthesis of M10c from M10b via Click chemistry opens the opportunity for the rhodamine system to be used as redox-active fluorescence probes especially in fluorescence confocal microscopy [28].…”
Section: Organic Small Elc Moleculesmentioning
confidence: 99%